2013
DOI: 10.1097/aln.0b013e3182833fcc
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Determining Hemoglobin Level Using Occlusion Spectroscopy in Patients with Severe Gastrointestinal Bleeding

Abstract: Background:In patients presenting with severe hemorrhage, the authors conducted an equivalence trial that compared noninvasive occlusion spectroscopy and the capillary blood method to determine hemoglobin level. Methods: This prospective observational study included patients admitted to their intensive care unit for gastrointestinal bleeding. A ring-shaped sensor, connected to a NBM-200MP (OrSense ® , Nes Ziona, Israel), was fitted onto the patient's thumb to intermittently measure hemoglobin (So t Hb). During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
(42 reference statements)
0
22
0
Order By: Relevance
“…The author is not supported by, nor maintains any financial interest in, any commercial activity that may be associated with the topic of this article. Bruno Riou Editorial Views you reach the conclusion of Coquin et al 2 study. In the near future, we need to answer the following questions: (1) Do we need continuous hemoglobin monitoring?…”
mentioning
confidence: 93%
“…The author is not supported by, nor maintains any financial interest in, any commercial activity that may be associated with the topic of this article. Bruno Riou Editorial Views you reach the conclusion of Coquin et al 2 study. In the near future, we need to answer the following questions: (1) Do we need continuous hemoglobin monitoring?…”
mentioning
confidence: 93%
“…Determining hemoglobin using a noninvasive hemoglobin monitoring device in ICU patients with severe gastrointestinal bleeding appears inaccurate for clinical decision making [4, 32 • ]. In ICU patients admitted for gastrointestinal hemorrhage, the NBM-200MP lacked accuracy compared with cHb regardless of the measurement site [4]. When a study of the Radical-7 in a similar situation was performed, its clinical performance and accuracy were also not acceptable.…”
Section: Icumentioning
confidence: 99%
“…The lights in wavelength ranging from 600 to 950 nm are emitted from the ten spectrally stabilized emitters and detected within sensor, and the hemoglobin concentration can be measured by analyzing the signals at these wavelengths [7]. NBM-200MP additionally displays plethysmography and oxygen saturation of hemoglobin, based on the association of lowperfusion oximetry combined with occlusion spectroscopy [4]. Several studies of the OrSense products have been conducted, but have shown inconsistent results with a wide variation in biases.…”
Section: Orsense Productsmentioning
confidence: 99%
See 2 more Smart Citations